Triboelectric Generator Based on Oriented Self-Assembled Peptide Microbelts - Vladislav Slabov; João Vidal; Pavel Zelenovskii; Svitlana Kopyl; Marco P. Soares dos Santos; Andrei Kholkin (Nanomaterials, 2022)
Along with piezoelectric nanogenerators, triboelectric nanogenerators (TENGs) collecting energy from mechanical vibrations proved to be simple, low-cost, and efficient sources of electricity for various applications. In view of possible biomedical applications, the search for TENGs made of biomolecular and biocompatible materials is demanding. Diphenylalanine (FF) microstructures are promising for these applications due to their unique characteristics and ability to form various morphologies (microribbons, spherical vesicles, fibrils, micro- and nanotubes, nanorods, etc.). In this work, we developed a contact-separate mode TENG based on arrays of oriented FF microbelts deposited by dip-coating technique and studied their performance under various temperature treatments. We show that these TENGs outperform piezoelectric nanogenerators based on FF microbelts in terms of short-circuit current (ISC), open-circuit voltage (VOC), and output power. It was found that bound water captured in FF nanochannels mainly affects VOC, whereas mobile water increases ISC. We also found that the cyclization of FF molecules increases the performance of TENG likely due to an increase in surface energy and surface flattening.